Modeling of a Gc-sensing element for the interfacial toughness of metal thin films on substrates - Jeon, Insu; Omiya, Masaki; Kishimoto, Kikuo; Asahina, Tadashi; Im, Seyoung (Sensors and actuators. A. Physical., 2005)
A new type of the sensitive specimen named 'Gc-sensing element'that can be fabricated, using the plain and general micro-fabrication process, is proposed and modeled to measure the interfacial toughness Gc of metal thin films on substrates. For the whole modeling process of the Gc-sensing element, the finite element method and the concepts of the linear elastic fracture mechanics are applied. Moreover, the verification for energy-release rates calculated from the linear elastic fracture analysis is carried out, using the elastic-plastic fracture analysis. The results of this research show that the Gc-sensing element provides a simple and convenient method for measuring the precise interfacial toughness of metal thin films on substrates.